Temperature and Humidity Monitoring Using DHT22 Sensor and Cayenne API - Adhiwibowo, Whisnumurti; Daru, April Firman; Hirzan, Alauddin Maulana (Jurusan Teknologi Informasi Universitas Semarang, 2020)
Internet of Thing is a new technology which enables small processing-capable devices to capture or retrieve information from a sensor and send the data to the central computer. This technology is useful for any sector especially agriculture, IoT can be used as monitoring or/and controlling the condition inside the cultivation. There are many kinds of agriculture cultivations, some of them have strict conditions due to the growth requirements. Oyster mushroom cultivation is one of many cultivations which requires strict temperature and humidity needed by oyster mushroom to growth optimal. The temperature inside the cultivation must be within 25 °C until 30 °C and humidity within 70% RH until 90% RH. Due to these strict requirements, the farmers required to check their cultivations every day and manually maintain the temperature and humidity, and this situation becomes a problem when the farmers own many cultivations. Hence, this research has a purpose to design an automatic monitoring system based on Internet of Things technology which utilizing the DHT22 sensor and Cayenne API as information retrieval medium to the computer. When using this device, the farmers can check their cultivation in the meantime without going inside the cultivation. This device will connect to the internet through wireless connectivity and send the captured information by the sensor to the farmers. The stored data from the cultivation can be exported as a CSV format if the farmers want to check the temperature and humidity statistic. The retrieved information from the sensor also displayed on the LCD attached to the device to ease the information reading near the cultivation.